ANALISIS KARAKTER DISIPLIN DAN KERJA KERAS PADA SISWA KELAS V SD NEGERI 161 PEKANBARU - Radiatul Adawiah; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is based on observations that were found in the fifth grade students of SD Negeri 161 Pekanbaru are still many students who throw trash out of place and there are still students who arrive late to school, there are students who do not do their homework, and there are still students who dress does not fit with school rules. This study has the objective to determine the character of discipline and hard work in class V SD Negeri 161 Pekanbaru. The research is descriptive quantitative research, using research instruments such as questionnaires and interviews. Characters discipline Elementary School fifth grade student 161 Pekanbaru in three indicator derived from the percentage of students' answers, the third indicator disciplinary character get good category that is on the discipline of time with a percentage indicator 79,37% and indicators of regulatory discipline with 82.84% and the percentage indicator of behavioral discipline earn a percentage 83.44%. Character hard work in class V SD Negeri 161 Pekanbaru in two indicator derived from the percentage of students, both indicators karaker hard work getting both categories namely on indicators of completing all tasks well and timely with the percentage of 79.28% and the indicator does not easily give up in completing the task with a percentage of 77.81%.Key Words: Character, Discipline, Work Hard